Analysis of the impact mechanisms and driving factors of urban spatial morphology on urban heat islands - Caiyi Huang; Ke Liu; Tianyi Ma; Hang Xue; Pengfei Wang; Lin Li (Scientific Reports)
Abstract The intensity of urban heat islands (UHI) is closely related to urban underlying surface characteristics. This study investigates the effects of underlying surfaces on land surface temperature (LST) in the highly urbanized central districts and rapidly developing peri-urban areas of Tianjin, China. Ten driving factors linked to urban spatial morphology, land surface, and socioeconomic conditions were selected from 2 and 3D perspectives. LST was derived using Landsat 8 and MODIS data from August 28, 2020. XGBoost and SHAP were applied to analyze the contributions of individual and interacting factors on LST. The results showed that: (1) In the central districts, the contributions of NDVI (0.89), BH (0.30), and Albedo (0.25) were the highest. In the peri-urban areas, the contributions of NDVI (0.90), Albedo (0.60), and NLI (0.42) were the highest. NDVI showed a significant negative correlation with LST in both areas, with a more pronounced cooling effect compared to other factors. (2) In the central districts, the combination of BH and BD had the greatest impact on LST, with cooling effects observed when BH > 20m and BD decreased. In the peri-urban areas, the combination of NDVI and PIS was most influential, with higher PIS increasing LST when NDVI < 0.5. (3) Urban spatial parameters had a weaker impact on LST in the peri-urban areas compared to the central districts, where socioeconomic parameters played a stronger role. Overall, 2D perspectives had a greater impact on LST than 3D perspectives. The findings highlight the need for tailored regulatory measures based on urban development stages.